(untitled) (Current Problems in Rail Vehicles, 2025)
Small-scale laboratory equipment with balls or discs representing the wheels and rails is often used in the development and testing of lubricants for the wheel–rail interface. Such devices are suitable, even necessary, for any standard test methodology, but they may not accurately represent all the conditions of actual wheel–rail contact; special test equipment of a larger scale can get closer to reality. This paper presents findings on the influence of flange lubricants on adhesion conditions, as they can be investigated on a full-scale roller rig. Adhesion characteristics (traction curves) are used for the evaluation, describing the adhesion conditions in greater completeness than just the time histories of the coefficient of friction at constant slip.